Aluminum alloy-carbon fiber SMC / BMC composite middle frame, preparation method and application thereof

CN122952529APending Publication Date: 2026-10-20SHENZHEN NO 1 FINE CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611271295.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

若铝合金外框与碳纤维复合中板分别加工后再进行连接,容易产生基准转换误差和累积装配误差,影响孔位精度、平面度和整机装配一致性;若在复合后再进行CNC加工,则铝合金与碳纤维复合材料的交界区域可能因加工而暴露,进一步增加湿气或腐蚀介质沿界面侵入的风险

Benefits of technology

1)本发明通过宏观机械锁合结构与模压流动填充相结合,使铝合金外框和碳纤维复合中板之间不仅依靠界面黏附,而且通过倒扣、贯穿铆固和齿形咬合承载,提高界面抗剥离、抗剪切和抗跌落起翘能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1787214230934-000002
    Figure REF-OBJ-1787214230934-000002
  • Figure REF-OBJ-1787214230934-000003
    Figure REF-OBJ-1787214230934-000003
  • Figure REF-OBJ-1787214230934-000004
    Figure REF-OBJ-1787214230934-000004
Patent Text Reader

Abstract

This invention belongs to the field of consumer electronics structural components and composite material molding technology. This invention provides an aluminum alloy-carbon fiber SMC / BMC composite mid-frame, including an aluminum alloy outer frame and a carbon fiber composite mid-plate disposed inside the aluminum alloy outer frame; a mechanical locking structure is provided on the side of the aluminum alloy outer frame facing the carbon fiber composite mid-plate; carbon fiber-containing SMC and / or BMC flow and fill the mechanical locking structure during molding and solidify to form a locking body; an insulating and anti-corrosion interface layer is provided between the aluminum alloy outer frame and the carbon fiber composite mid-plate; after molding and curing, the integral part is CNC machined and edge-sealed. This composite mid-frame can improve the peel and shear resistance between the aluminum alloy outer frame and the carbon fiber composite mid-plate, reduce the risk of galvanic corrosion between the aluminum alloy and carbon fiber, and improve the lightweight, dimensional accuracy, drop resistance, and long-term reliability of the composite mid-frame.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of consumer electronics structural components and composite material forming technology, and in particular to an aluminum alloy-carbon fiber SMC / BMC composite midframe, its preparation method and application. Background Technology

[0002] As electronic terminal devices evolve towards thinner, lighter, larger screens, higher integration, and higher reliability, composite mid-frames, as crucial components for overall structural support, assembly positioning, and aesthetic load-bearing, must simultaneously meet requirements such as lightweight design, high rigidity, high dimensional accuracy, drop impact resistance, and consistent appearance. In portable electronic devices such as mobile phones, tablets, laptops, drones, robotic terminals, and AR / VR devices, existing mid-frames are typically made of aluminum alloy. While aluminum alloy mid-frames offer advantages such as mature processing technology, high CNC forming precision, and good surface anodizing or spraying effects, they still have limitations in further reducing overall weight, improving bending rigidity, and reinforcing areas with openings. Especially when there are numerous structural elements such as side key holes, port holes, camera clearance areas, and connection holes, a single aluminum alloy mid-frame is susceptible to localized thinning, weakening from openings, and complex stress environments, making it difficult to simultaneously achieve both lightweight design and structural strength.

[0003] Carbon fiber composites, characterized by low density, high specific strength, and high specific stiffness, have been used in the housings and structural components of some electronic devices to improve their lightweight and mechanical properties. However, existing solutions for combining carbon fiber composites with aluminum alloy frames often employ adhesive bonding, thermoforming, or surface micropore bonding. These methods are prone to insufficient interfacial bonding strength in areas of concentrated stress, such as thin-walled frames, corner areas, perimeters of holes, and large camera openings. Under prolonged drop impacts, bending loads, thermal cycling, or humid environments, interfacial delamination, edge warping, or localized delamination may occur between the aluminum alloy and carbon fiber composites, affecting the overall reliability of the phone's frame.

[0004] Furthermore, carbon fiber is conductive. When carbon fiber composites come into direct contact with aluminum alloys and form conductive pathways in electrolyte environments such as moisture, sweat, and salt spray, galvanic corrosion is likely to occur. For thin-walled, easily exposed-edge mid-frame structural components with aesthetic requirements, interfacial corrosion not only reduces the reliability of the connection between the aluminum alloy and carbon fiber composites but may also lead to edge bulging, coating failure, or aesthetic defects. Therefore, reducing direct conductive contact and improving interfacial insulation and corrosion resistance are urgent problems to be solved when aluminum alloys and carbon fiber composites are combined.

[0005] Meanwhile, composite frames typically require precision structures such as assembly reference surfaces, side key holes, port holes, camera clearance positions, and connection holes. If the aluminum alloy outer frame and the carbon fiber composite middle plate are machined separately before being connected, reference conversion errors and cumulative assembly errors are likely to occur, affecting hole accuracy, flatness, and overall assembly consistency. If CNC machining is performed after the composite is formed, the interface between the aluminum alloy and carbon fiber composite materials may be exposed due to machining, further increasing the risk of moisture or corrosive media intrusion along the interface. Therefore, existing technologies still lack a composite frame structure and its fabrication method that can simultaneously achieve high-strength connection, galvanic corrosion resistance, forming efficiency, machining accuracy, and boundary reliability of aluminum alloy and carbon fiber composite materials. Summary of the Invention

[0006] The purpose of this invention is to address the shortcomings of existing composite frames in terms of lightweighting, structural rigidity, interface connection reliability, and corrosion resistance by providing an aluminum alloy-carbon fiber SMC / BMC composite frame, its preparation method, and its applications. This composite frame achieves a stable bond between the aluminum alloy outer frame and the carbon fiber composite middle plate through a mechanically interlocking connection, coupled with an insulating and corrosion-resistant interface layer and edge sealing structure. This allows the carbon fiber composite material to form a stable bond with the aluminum alloy outer frame during molding and curing, thereby improving the composite frame's peel resistance, shear resistance, resistance to damp heat corrosion, and processing and assembly precision, meeting the requirements for lightweight, high-strength, and long-term reliable use of composite frames.

[0007] To achieve the above-mentioned objectives, the present invention provides the following technical solution: The present invention provides an aluminum alloy-carbon fiber SMC / BMC composite mid-frame, comprising an aluminum alloy outer frame and a carbon fiber composite mid-plate disposed inside the aluminum alloy outer frame; The aluminum alloy outer frame is provided with a mechanical locking structure on the side facing the carbon fiber composite middle plate; The carbon fiber composite middle plate is formed by molding and curing carbon fiber-containing SMC and / or BMC; during the molding and curing process, a portion of the SMC and / or BMC flows into the mechanical locking structure and is cured to form a locking body, thereby forming a mechanical locking connection between the aluminum alloy outer frame and the carbon fiber composite middle plate, constituting an integral part; The integrated component, after being CNC machined, has one or more of the following: an assembly reference surface, side key holes, port holes, camera clearance positions, and connection holes; An insulating and corrosion-resistant interface layer is provided between the aluminum alloy outer frame and the carbon fiber composite middle plate.

[0008] Preferably, the aluminum alloy frame is made of aluminum-magnesium alloy, aluminum-magnesium-silicon alloy, or aluminum-zinc alloy. One or more of magnesium-based aluminum alloys, aluminum-zinc-magnesium-copper-based aluminum alloys, and aluminum-silicon-based cast aluminum alloys; The mechanical locking structure is one or more of the following: dovetail groove, T-groove, serrated groove, undercut hole, undercut blind hole, and through hole.

[0009] Preferably, the aluminum alloy outer frame also has a roughened interface in the area where the mechanical locking structure is set; The average profile micro-pitch RSm of the roughened interface is 0.8~10μm, and the ten-point height Rz is 0.2~5μm; and / or, the roughened interface has an inverted snap-like microstructure, a reverse-entry bridge-like microstructure, or a concave-convex interlocking microstructure.

[0010] Preferably, the insulating and corrosion-resistant interface layer includes an inorganic insulating layer disposed on the surface of the aluminum alloy frame, and a covering insulating layer disposed on the inorganic insulating layer; The inorganic insulating layer is one or more of the following: insulating oxide layer, ceramic layer and chemical conversion layer; The covering insulation layer is one or more of the following: coupling primer layer, resin enrichment layer, inorganic filler insulation layer, glass fiber isolation layer and aramid isolation layer; The total thickness of the insulating and anti-corrosion interface layer is 5~100μm, wherein the thickness of the inorganic insulating layer is 2~30μm, and the thickness of the covering insulating layer is 3~70μm; The volume resistivity of the insulating and corrosion-resistant interface layer is 10. 8 ~10 14 Ω·cm.

[0011] Preferably, the matrix resin of the carbon fiber composite middle plate is one or more of epoxy resin, vinyl ester resin, benzoxazine resin, cyanate ester resin and phenolic resin. The carbon fiber in the carbon fiber composite plate has a mass fraction of 20-70% and a length of 3-50 mm.

[0012] Preferably, the carbon fiber composite midplate includes a planar load-bearing area formed by SMC and a localized reinforcing area formed by BMC. The planar load-bearing area is located on the main body panel area inside the aluminum alloy outer frame; The local reinforcement area is located at one or more of the following positions: corner, connecting column, local rib, perimeter of hole, and perimeter of large opening of camera.

[0013] Preferably, an interface is formed between the aluminum alloy outer frame and the carbon fiber composite middle plate, and the area exposed after CNC machining in the interface is provided with an edge sealing layer. The edge sealing layer is an epoxy edge sealing layer, a fluorinated polymer edge sealing layer, a polyimide edge sealing layer, and a Pyrite edge sealing layer. One or more of the forest edge sealing layers, with a thickness of 5~80μm.

[0014] This invention also provides the preparation of the aforementioned aluminum alloy-carbon fiber SMC / BMC composite mobile phone frame. The method includes the following steps: S1. Provide an aluminum alloy outer frame substrate, and process a mechanical locking structure on the side of the aluminum alloy outer frame substrate facing the carbon fiber composite middle plate; S2. The aluminum alloy outer frame substrate with mechanical locking structure obtained in step S1 is cleaned and roughened on the side facing the carbon fiber composite middle plate, and an insulating and anti-corrosion interface layer is constructed on this side surface to obtain the aluminum alloy outer frame. S3. Place the aluminum alloy outer frame in the mold, and place the SMC sheet containing carbon fiber and / or BMC pellets inside the aluminum alloy outer frame corresponding to the forming area of ​​the carbon fiber composite middle plate. Perform molding and curing treatment, so that the SMC sheet and / or BMC pellets flow into the mechanical locking structure and solidify to form a locking body during the molding and curing process. At the same time, the carbon fiber composite middle plate is solidified to form a carbon fiber composite middle plate, thereby forming a mechanical locking connection between the aluminum alloy outer frame and the carbon fiber composite middle plate to obtain an integral part. S4. The integral part is subjected to post-curing treatment and CNC machining in sequence to form one or more of the following: assembly reference surface, side key hole, port hole, camera clearance position and connection hole. S5. The junction between the exposed aluminum alloy frame and the carbon fiber composite middle plate after CNC machining. Edge sealing is performed to obtain an aluminum alloy-carbon fiber SMC / BMC composite mid-frame.

[0015] Preferably, the temperature of the molding and curing process in step S3 is 120~180℃, the pressure is 3~30MPa, the holding time is 60~900s, and vacuum-assisted degassing is used during the molding and curing process.

[0016] Preferably, the post-curing treatment in step S4 is performed at a temperature of 140~170℃ for 40~90 minutes.

[0017] The present invention also provides the application of the aluminum alloy-carbon fiber SMC / BMC composite midframe in mobile phones, tablets, laptops, drones, robot terminals, AR or VR devices.

[0018] The beneficial effects of this invention include the following: 1) This invention combines a macroscopic mechanical locking structure with molded flow filling, so that the aluminum alloy outer frame and the carbon fiber composite middle plate not only rely on interface adhesion, but also rely on undercut, through riveting and toothed interlocking to improve the interface's resistance to peeling, shearing and drop warping.

[0019] 2) The present invention sets an insulating and anti-corrosion interface layer between the aluminum alloy outer frame and the carbon fiber composite middle plate, which can reduce the probability of direct conductive contact between carbon fiber and aluminum alloy and reduce the risk of galvanic corrosion in humid, sweat or salt spray environments.

[0020] 3) This invention can form a planar load-bearing area through SMC and a local reinforcement area through BMC, so that the composite frame can obtain a better planar load-bearing capacity in the main plate area, while obtaining better filling and reinforcement effects in local complex areas such as corners, connecting columns, local ribs, hole perimeters and camera large opening perimeters, which is conducive to taking into account lightweight, structural strength and complex structure forming ability.

[0021] 4) In this invention, after the aluminum alloy outer frame and the carbon fiber composite middle plate are molded and cured to form an integral part, the integral part is then CNC machined. This helps to reduce the reference conversion error caused by separate processing and assembly, and improve the hole position accuracy, flatness and overall assembly consistency.

[0022] 5) After CNC machining, the exposed area at the junction of the aluminum alloy outer frame and the carbon fiber composite middle plate is sealed, which can reduce the risk of moisture, sweat or salt spray intrusion along the junction and improve the boundary reliability of the composite middle frame. Attached Figure Description

[0023] Figure 1 This is a schematic diagram of the overall structure of the aluminum alloy-carbon fiber SMC / BMC composite frame of the present invention; Figure 2 This is a cross-sectional schematic diagram of the dovetail groove / inverted groove mechanical locking structure in this invention; Figure 3 This is a partial cross-sectional schematic diagram of the rivet-shaped locking body formed inside the through hole in this invention; Figure 4 This is a schematic diagram of the insulating and anti-corrosion interface layer structure in this invention; Figure 5 This is a schematic diagram showing the arrangement of the SMC planar load-bearing area and the BMC local reinforcement area in this invention; Figure 6 This is a schematic diagram showing the assembly reference surface and hole structure formed by CNC machining of the integral part in this invention; Figure 7 This is a schematic diagram of the structure in this invention where an edge sealing layer is provided at the junction of the aluminum alloy outer frame and the carbon fiber composite middle plate. Detailed Implementation

[0024] The present invention provides an aluminum alloy-carbon fiber SMC / BMC composite mid-frame, comprising an aluminum alloy outer frame and a carbon fiber composite mid-plate disposed inside the aluminum alloy outer frame; The aluminum alloy outer frame is provided with a mechanical locking structure on the side facing the carbon fiber composite middle plate; The carbon fiber composite mid-plate is formed by compression molding and curing of carbon fiber-containing SMC and / or BMC; during the compression molding and curing process, a portion of the SMC and / or BMC flows into the mechanical interlocking structure. Inside, it solidifies to form a locking body, thereby forming a bond between the aluminum alloy outer frame and the carbon fiber composite middle plate. Mechanical locking connection, forming a single unit; The integrated component, after being CNC machined, has one or more of the following: an assembly reference surface, side key holes, port holes, camera clearance positions, and connection holes; An insulating and corrosion-resistant interface layer is provided between the aluminum alloy outer frame and the carbon fiber composite middle plate.

[0025] In this invention, the aluminum alloy outer frame is preferably one or more of the following: aluminum-magnesium alloy, aluminum-magnesium-silicon alloy, aluminum-zinc-magnesium alloy, aluminum-zinc-magnesium-copper alloy, and aluminum-silicon cast aluminum alloy. More preferably, it is one or more of the following: 6061-T6, 6063-T6, 6082-T6, and 7075-T6.

[0026] In this invention, the mechanical locking structure is preferably one or more of the following: dovetail groove, T-groove, serrated groove, undercut hole, undercut blind hole, and through hole.

[0027] In this invention, when the mechanical locking structure is a dovetail groove and / or a T-groove, the opening width of the mechanical locking structure is preferably 0.1~1.2mm, more preferably 0.5~1mm, and even more preferably 0.8mm; the ratio of the cavity bottom width to the opening width is preferably 1.05~3:1, more preferably 1.5~2.5:1, and even more preferably 2:1; the structural depth is preferably 0.1~1.5mm, more preferably 0.5~1mm, and even more preferably 0.8mm; the pitch between adjacent mechanical locking structures is preferably 0.3~8mm, more preferably 2~6mm, and even more preferably 4~5mm. When the mechanical locking structure is a sawtooth groove, the tooth height of the sawtooth groove is preferably 0.1~1.5mm, more preferably 0.5~1mm, and even more preferably 0.6~0.8mm; the tooth pitch is preferably 0.3~8mm, more preferably 3~7mm, and even more preferably 4~5mm. When the mechanical locking structure is a through hole and / or a reverse hole, the equivalent hole diameter of the mechanical locking structure is preferably 0.2~1.5mm, more preferably 0.5~1mm, and even more preferably 0.6~0.8mm; the hole spacing is preferably 1~10mm, more preferably 4~8mm, and even more preferably 5~6mm. When the mechanical locking structure is an inverted blind hole, the inlet diameter is preferably 0.4~0.5mm, more preferably 0.45mm, the bottom diameter is preferably 0.7~0.85mm, more preferably 0.75mm, and the hole depth is preferably 0.6~0.7mm, more preferably 0.65mm.

[0028] In this invention, the mechanical locking structure is preferably disposed at one or more positions on the inner peripheral wall, corner transition section, rib connection section, periphery of the large opening of the camera, periphery of the button hole and periphery of the port hole of the aluminum alloy outer frame.

[0029] In this invention, the aluminum alloy outer frame preferably also has a roughened interface in the area where the mechanical locking structure is set; The average profile micro-interface spacing RSm of the roughened interface is preferably 0.8~10μm, and more preferably... The value is 2~8μm, more preferably 4~6μm; the ten-point height Rz is preferably 0.2~5μm, more preferably... 1~4μm, more preferably 2~3μm; and / or, the roughened interface preferably has an inverted button-like microstructure, Reverse-entry bridge-like microstructures or concave-convex interlocking microstructures.

[0030] In this invention, the reverse-entry bridge-like microstructure refers to a microscopic contour with inward folding, bridging, or partially obstructing openings at the edge of the micro-pit or the re-solidified ridge, which produces mechanical backing at the microscopic scale after the molding resin enters.

[0031] In this invention, the roughened interface is preferably formed by one or more of the following methods: sandblasting, chemical etching, mechanical rolling, and laser texturing.

[0032] In this invention, the insulating and anti-corrosion interface layer preferably includes an inorganic insulating layer disposed on the surface of the aluminum alloy frame and a covering insulating layer disposed on the inorganic insulating layer; The inorganic insulating layer is preferably one or more of an insulating oxide layer, a ceramic layer, and a chemical conversion layer; The covering insulation layer is preferably one or more of the following: coupling primer layer, resin enrichment layer, inorganic filler insulation layer, glass fiber isolation layer and aramid isolation layer; The total thickness of the insulating and anti-corrosion interface layer is preferably 5~100μm, more preferably 20~80μm, and even more preferably 40~60μm; wherein, the thickness of the inorganic insulating layer is preferably 2~30μm, more preferably 10~25μm, and even more preferably 15~20μm; the thickness of the covering insulating layer is preferably 3~70μm, more preferably 10~50μm, and even more preferably 20~40μm. The volume resistivity of the insulating and corrosion-resistant interface layer is preferably 10. 8~10 14 Ω·cm, further preferably 10 10 ~10 13 Ω·cm, more preferably 10 11 ~10 12 Ω·cm.

[0033] In this invention, the insulating and anti-corrosion interface layer is preferably constructed by one or more of the following methods: anodic oxidation, micro-arc oxidation, plasma electrolytic oxidation, chemical conversion, silane coupling treatment, ceramic-filled resin coating, and insulating fiber sheet lamination.

[0034] In this invention, the insulating and anti-corrosion interface layer can reduce the probability of carbon fiber directly contacting aluminum alloy and improve the continuity of resin at the interface during molding. The inorganic insulating layer is used to isolate the direct electrical contact between aluminum alloy and carbon fiber, and the covering insulating layer is used to improve resin continuity, buffer thermal expansion differences, and block moisture migration. The glass fiber isolation layer or aramid isolation layer in the covering insulating layer can also form a tough transition in the mechanically locked area, reducing the risk of crack propagation at the interface edge after CNC machining.

[0035] In this invention, the matrix resin of the carbon fiber composite middle plate is preferably epoxy resin or vinyl ester. One or more of the following: resin, benzoxazine resin, cyanate ester resin and phenolic resin; The mass fraction of the carbon fiber in the carbon fiber composite plate is preferably 20-70%, more preferably 30-50%, and even more preferably 40%; the length of the carbon fiber is preferably 3-50 mm, more preferably 20-40 mm, and even more preferably 30 mm.

[0036] In this invention, the carbon fiber composite middle plate preferably has a non-conductive reinforcement area in the antenna avoidance area or the electromagnetically sensitive area; the non-conductive reinforcement area is preferably one or more of the following: a carbon fiber resin area, a glass fiber reinforced resin area, or an aramid fiber reinforced resin area.

[0037] In this invention, the carbon fiber composite mid-plate preferably includes a planar load-bearing area formed by SMC and a local reinforcement area formed by BMC. This combination enables the composite mid-frame to have both high specific stiffness and forming efficiency, and to achieve more adequate filling in local complex areas. The planar load-bearing area is preferably located on the main body plate area inside the aluminum alloy outer frame; The local reinforcement area is preferably located at one or more of the following positions: corner, connecting column, local rib, periphery of hole, and periphery of camera opening.

[0038] In this invention, a junction is preferably formed between the aluminum alloy outer frame and the carbon fiber composite middle plate, and the area exposed after CNC machining in the junction is preferably provided with an edge sealing layer; The edge sealing layer is preferably one or more of epoxy edge sealing layer, fluorinated polymer edge sealing layer, polyimide edge sealing layer and phenelzine edge sealing layer; the thickness of the edge sealing layer is preferably 5~80μm, more preferably 20~60μm, and even more preferably 30~40μm.

[0039] The present invention also provides a method for preparing the aforementioned aluminum alloy-carbon fiber SMC / BMC composite midframe, comprising the following steps: S1. Provide an aluminum alloy outer frame substrate, and process a mechanical locking structure on the side of the aluminum alloy outer frame substrate facing the carbon fiber composite middle plate; S2. The aluminum alloy outer frame substrate with mechanical locking structure obtained in step S1 is cleaned and roughened on the side facing the carbon fiber composite middle plate, and an insulating and anti-corrosion interface layer is constructed on this side surface to obtain the aluminum alloy outer frame. S3. Place the aluminum alloy outer frame in the mold, and place the SMC sheet and / or BMC pellet containing carbon fiber inside the aluminum alloy outer frame corresponding to the forming area of ​​the carbon fiber composite middle plate. Perform molding and curing treatment, so that the SMC sheet and / or BMC pellet flow into the mechanical lock during the molding and curing process. The aluminum alloy is then cured and solidified to form a locking body within the structure, while simultaneously curing to form a carbon fiber composite middle plate, thereby enabling the aluminum alloy to... The outer frame and the carbon fiber composite middle plate are mechanically locked together to form a single piece; S4. The integral part is subjected to post-curing treatment and CNC machining in sequence to form one or more of the following: assembly reference surface, side key hole, port hole, camera clearance position and connection hole. S5. The junction between the exposed aluminum alloy frame and the carbon fiber composite middle plate after CNC machining. Edge sealing is performed to obtain an aluminum alloy-carbon fiber SMC / BMC composite mid-frame.

[0040] In this invention, the aluminum alloy outer frame substrate mentioned in step S1 is preferably produced by extrusion, forging, or die casting. The mechanical locking structure is preferably formed by one or more of the following methods: CNC milling, drilling, broaching, roll forming, laser processing, and electrical discharge machining.

[0041] In this invention, the cleaning in step S2 preferably includes alkaline degreasing, deionized water washing, and drying.

[0042] In this invention, the temperature of the molding and curing process in step S3 is preferably 120~180℃, more preferably 140~160℃, and even more preferably 150℃; the pressure is preferably 3~30MPa, more preferably 10~20MPa, and even more preferably 15MPa; the holding time is preferably 60~900s, more preferably 200~700s, and even more preferably 400~600s; and vacuum-assisted degassing is preferably used during the molding and curing process.

[0043] In this invention, the vacuum-assisted venting is preferably performed at the initial stage of mold closing; the vacuum pressure is preferably -0.06 to -0.095 MPa, more preferably -0.08 MPa, and the maintenance time is preferably 10 to 120 s, more preferably 50 to 100 s, and more preferably 60 to 80 s.

[0044] In this invention, the temperature of the post-curing treatment in step S4 is preferably 140~170℃, more preferably 150~160℃, and even more preferably 155℃; the time is preferably 40~90min, more preferably 50~80min, and even more preferably 60~70min.

[0045] In this invention, the CNC machining in step S4 is preferably one or more of the following: sidewall finishing, plane finishing, hole machining, chamfering, and local step machining.

[0046] In this invention, the edge sealing process in step S5 preferably includes cleaning the junction, applying edge sealing material, scraping or wiping off excess edge sealing material, and curing into a film; the edge sealing material is preferably one or more of two-component epoxy edge sealing adhesive, UV-cured epoxy edge sealing adhesive, fluorinated polymer solution, polyimide precursor solution, and Piriton deposition layer.

[0047] In this invention, after the edge sealing process described in step S5, it is preferable that the integral part can also be further processed. One or more of the following post-treatment methods for appearance: low-temperature spraying, PVD decorative film, electrophoresis, and film lamination, to suppress... Electrolyte or moisture can penetrate along the interface. The present invention also provides the application of the aluminum alloy-carbon fiber SMC / BMC composite midframe in mobile phones, tablets, laptops, drones, robot terminals, AR or VR devices.

[0048] The technical solution provided by the present invention will be described in detail below with reference to the embodiments, but it should not be taken as fact. These are understood as limiting the scope of protection of this invention.

[0049] The carbon fiber-containing SMC sheet, by total mass, comprises 52.0 wt% PAN-based chopped carbon fibers, 31.5 wt% toughening epoxy resin system, 7.0 wt% spherical silica insulating inorganic filler, 8.5 wt% dicyandiamide / aromatic urea compound curing agent system, and 1.0 wt% molding aid; the chopped carbon fibers have a length of 12 mm and a single filament diameter of 7 μm; the toughening epoxy resin system consists of bisphenol F epoxy resin (epoxy equivalent of 170 g / eq), tetraglycidyl chloride, and acetone. The masterbatch is composed of glycerol-based diaminodiphenylmethane, polyethersulfone, and acrylate-based core-shell rubber in a mass ratio of 100:35:18:10; the polyethersulfone has a weight-average molecular weight of 45,000; the average particle size of the core-shell rubber particles in the acrylate-based core-shell rubber masterbatch is 0.18 μm; in the dicyandiamide / aromatic urea compound curing agent system, the mass ratio of dicyandiamide to aromatic urea is 100:15, and the aromatic urea is toluene-based urea; the molding aid is zinc stearate and polyether-modified polydimethylsiloxane in a mass ratio of 4:1.

[0050] The carbon fiber-containing BMC aggregate, by total mass, comprises 36.0 wt% chopped carbon fibers, 42.5 wt% toughening epoxy resin system, 12.0 wt% spherical silica / alumina composite insulating inorganic filler, 8.2 wt% dicyandiamide / imidazolium compound curing agent system, and 1.3 wt% molding aids; the chopped carbon fibers have a length of 6 mm and a single filament diameter of 7 μm; the toughening epoxy resin system consists of bisphenol A epoxy resin (epoxy equivalent of 186 g / eq), bisphenol F epoxy resin (epoxy equivalent of 170 g / eq), polyurethane modified epoxy resin, and polyphenolic resin, by mass... The ratio is 45:35:12:8; the polyurethane-modified epoxy resin is a terminal epoxy-based polyether polyurethane-modified epoxy resin obtained by reacting polytetrahydrofuran ether diol, isophorone diisocyanate, and bisphenol F type liquid epoxy resin, with an epoxy equivalent of 480 g / eq and a viscosity of 65000 mPa·s at 25℃; the polyphenolic resin is a bisphenol A type polyphenolic resin with a weight-average molecular weight of 52000; in the spherical silica / alumina composite insulating inorganic filler, the mass ratio of spherical silica to alumina is 3:2; in the dicyandiamide / imidazolium compound curing agent system, the mass ratio of dicyandiamide to imidazolium is 100:8, and the imidazolium is... 2-Ethyl-4-methylimidazolium tetraphenylborate; the molding aid includes zinc stearate and polyether-modified poly... Dimethylsiloxane, with a mass ratio of 4:1.

[0051] Example 1

[0052] First, a 6061-T6 aluminum alloy frame substrate with external dimensions of 160.20mm × 75.80mm × 1.00mm is provided. A mechanical locking structure is formed on the side of the aluminum alloy frame substrate facing the carbon fiber composite middle plate using CNC milling. The mechanical locking structure includes dovetail grooves continuously arranged along the inner circumferential wall of the aluminum alloy frame and through holes located at the four corners and the middle of the long side. The dovetail grooves have an opening width of 0.42mm, a cavity bottom width of 0.78mm, a structural depth of 0.48mm, and a pitch of 2.60mm between adjacent dovetail grooves. The through holes have an equivalent aperture of 0.65mm and a spacing of 5.80mm between adjacent through holes.

[0053] Subsequently, the surface of the aluminum alloy outer frame substrate with the mechanical locking structure facing the carbon fiber composite middle plate was sequentially subjected to degreasing cleaning, deionized water washing, drying, and roughening treatment. The degreasing cleaning used a composite degreasing solution comprising 3.0% sodium carbonate, 1.5% fatty alcohol polyoxyethylene ether, and the balance deionized water. The fatty alcohol polyoxyethylene ether was AEO-9, and the mass ratio of sodium carbonate to fatty alcohol polyoxyethylene ether was 2:1. The degreasing cleaning temperature was 55℃, and the degreasing cleaning time was 6 minutes. The drying temperature was 80℃, and the time was 12 minutes. The roughening treatment was carried out by fine sand blasting with white corundum as the blasting medium, a particle size of 120 mesh, a blasting pressure of 0.35 MPa, a blasting distance of 120 mm, and a blasting time of 18 seconds. After blasting, the average profile micro-interval RSm of this side surface was 3.5 μm, and the ten-point height Rz was 1.6 μm. Then, the roughened aluminum alloy frame substrate was subjected to plasma electrolytic oxidation treatment. The electrolyte was an aqueous solution containing 8 g / L sodium silicate, 3 g / L potassium hydroxide, and 2 g / L sodium hexametaphosphate. The treatment voltage was 420 V, and the current density was 6.5 A / dm³. 2 The processing time is 4 minutes, forming a ceramic oxide layer with a thickness of 8.2 μm, which serves as an inorganic insulating layer. Then, a 1% (w / w) solution of γ-glycidyl etheroxypropyltrimethoxysilane ethanol / water solution (ethanol to water mass ratio 95:5) is coated onto the surface of the ceramic oxide layer using a dip-coating method. After coating, it is dried at 90°C for 10 minutes to form a coupling undercoating layer with a thickness of 0.3 μm. A surface density of 25 g / m² is then laid on top of the coupling undercoating layer. 2 A glass fiber insulating layer is formed, and SMC resin is then impregnated into the glass fiber insulating layer during subsequent molding to form a covering insulating layer with a total equivalent thickness of 25 μm, thus obtaining a volume resistivity of 10. 10 An insulating and corrosion-resistant interface layer with an Ω·cm thickness is used to obtain an aluminum alloy outer frame.

[0054] Next, the aluminum alloy outer frame is placed in the mold, which has a positioning cavity adapted to the shape of the aluminum alloy outer frame and a forming cavity corresponding to the carbon fiber composite middle plate. The dimensions of the forming cavity are 150.6mm × 66.3mm × 0.62mm. 18.6g of SMC sheet containing carbon fiber is placed inside the aluminum alloy outer frame, corresponding to the forming area of ​​the main plate of the carbon fiber composite middle plate. After the mold is closed, a molding and curing treatment is performed. The molding and curing treatment temperature is 148℃, the pressure is 8.5MPa, and the holding time is 420s. Vacuum-assisted venting is used in the initial stage of mold closing. Specifically, when the mold is closed to a pre-mold gap of 0.8mm, a vacuum is drawn to -0.085MPa and maintained for 45s. Then, the mold is closed and pressure is applied. The vacuum is maintained for the first 120s of the holding stage. During the molding and curing process, the SMC sheet flows under heat and pressure. A portion of the SMC material flows into the dovetail groove and through-hole, forming a locking body embedded in the mechanical locking structure after curing. Simultaneously, the remaining SMC material cures to form a carbon fiber composite middle plate, thereby creating a mechanical locking connection between the aluminum alloy outer frame and the carbon fiber composite middle plate, resulting in a single integrated component. For the through-hole area, the SMC material fills the through-hole to form a rivet-like locking body; for the dovetail groove area, the SMC material fills the dovetail groove to form an inverted embedded locking body.

[0055] Finally, the resulting monolithic part undergoes post-curing at 155℃ for 70 minutes. After post-curing, the monolithic part is CNC machined to form the assembly reference surface, side key holes, port holes, camera clearance area, and connection holes. During CNC machining, 0.12mm of allowance is removed from the sidewalls and 0.05mm of allowance is removed from the planes.

[0056] After CNC machining, a localized exposed area exists at the junction between the aluminum alloy outer frame and the carbon fiber composite middle plate. This exposed area is then sealed with an edge-sealing adhesive composed of bisphenol F epoxy resin (epoxy equivalent of 170 g / eq), alicyclic amine curing agent, nano-silica, and glycidyl ether silane in a mass ratio of 100:32:3:1. The nano-silica has an average particle size of 20 nm. The alicyclic amine curing agent is an isophorone diamine-modified alicyclic amine adduct with an amine value of 400 mg KOH / g, an active hydrogen equivalent of 100 g / eq, and a viscosity of 800 mPa·s at 25°C. The glycidyl ether silane is γ-glycidyl etheroxypropyltrimethoxysilane. After dispensing, the adhesive is cured at 80°C for 40 min to form a 14 μm thick epoxy edge-sealing layer, resulting in the aluminum alloy-carbon fiber SMC / BMC composite middle frame.

[0057] The interfacial shear strength of the aluminum alloy-carbon fiber SMC / BMC composite frame obtained in this embodiment was tested to be 31.8 MPa; after being treated under 85℃ and 85%RH humid heat conditions for 240 h, the interfacial shear strength retention rate was 92.1%; after 96 h of neutral salt spray testing, the edge corrosion expansion width was 0.12 mm; the weight of the obtained composite mobile phone frame was 11.86 g, which is 12.1% lower than that of the reference part of the same size made of all-aluminum 6061.

[0058] Example 2

[0059] First, a 7075-T6 aluminum alloy frame base with dimensions of 161.00mm × 76.20mm × 0.95mm is provided. A mechanical locking structure is formed on the side of the aluminum alloy frame base facing the carbon fiber composite middle plate using CNC milling and drilling. The mechanical locking structure includes a T-slot located inside the aluminum alloy frame and undercut blind holes located near corners, the periphery of button holes, and the periphery of the large camera opening. The T-slot has an opening width of 0.36mm, a bottom width of 0.92mm, a bottom width to opening width ratio of 2.56:1, and a structural depth of 0.62mm. The undercut blind holes have an inlet diameter of 0.44mm, a bottom diameter of 0.82mm, and a hole depth of 0.70mm.

[0060] Subsequently, the surface of the aluminum alloy outer frame substrate with the mechanical locking structure facing the carbon fiber composite middle plate was sequentially subjected to degreasing cleaning, deionized water washing, drying, and roughening treatment. The degreasing cleaning used a composite degreasing solution comprising 2.5% sodium hydroxide by mass, 1.0% sodium metasilicate solution by mass, and the remainder deionized water, wherein the mass ratio of sodium hydroxide to sodium metasilicate was 5:2, the degreasing cleaning temperature was 50℃, and the degreasing cleaning time was 5 min; the drying temperature was 75℃, and the time was 10 min; the roughening treatment was performed using laser texturing with a laser wavelength of 1064 nm, a pulse width of 80 ns, a single pulse energy of 0.18 mJ, a scanning interval of 40 μm, and a scanning speed of 800 mm / s. After the roughening treatment, the average profile micro-interval RSm of this side surface was 4.2 μm, and the ten-point height Rz was 2.4 μm. Then, the roughened aluminum alloy frame substrate was subjected to sulfuric acid anodizing treatment. The electrolyte was a 180 g / L sulfuric acid aqueous solution, the treatment voltage was 16 V, and the current density was 1.3 A / dm³. 2The processing time is 18 minutes, forming an insulating oxide layer with a thickness of 10.5 μm, which serves as an inorganic insulating layer. A ceramic-filled epoxy insulating primer is then coated onto the surface of the insulating oxide layer. By total mass, the ceramic-filled epoxy insulating primer comprises: 32 wt% bisphenol A epoxy resin, 18 wt% bisphenol F epoxy resin, 28 wt% spherical alumina, 12 wt% boehmite, 7 wt% latent imidazole adduct, 2 wt% glycidyl ether silane, and 1 wt% leveling agent. The epoxy equivalents of bisphenol A epoxy resin and bisphenol F epoxy resin were 186 g / eq and 170 g / eq, respectively. The average particle size of the spherical alumina was 1.2 μm, and the average particle size of the boehmite was 0.5 μm. The latent imidazole adduct was obtained by mixing 2-ethyl-4-methylimidazolium with bisphenol A type epoxy resin E-51 at a mass ratio of 1:5 and reacting at 100℃ for 2 h. The glycidyl ether silane was γ-glycidyl etheroxypropyltrimethoxysilane, and the leveling agent was polyether-modified polydimethylsiloxane leveling agent BYK-333. The coating method was blade coating, and after coating, it was cured at 110℃ for 15 min to form a 18 μm thick covering insulating layer, thus obtaining a volume resistivity of 10 Ω·cm. 8 An insulating and corrosion-resistant interface layer with an Ω·cm thickness is used to obtain an aluminum alloy outer frame.

[0061] Next, the aluminum alloy frame is placed in a mold. The mold has a positioning cavity that matches the shape of the aluminum alloy frame and a forming cavity that corresponds to the carbon fiber composite middle plate. The dimensions of the forming cavity are 151.20mm × 66.50mm × 0.58mm. 14.2g of carbon fiber-containing BMC pellets are placed inside the aluminum alloy frame in the forming area corresponding to the carbon fiber composite middle plate. Some of the BMC pellets are mainly arranged at corners, around button holes, connecting column areas, and around the large opening of the camera to form local reinforcement areas.

[0062] After mold closing, compression molding and curing are performed at a temperature of 156℃, a pressure of 12.0MPa, and a holding time of 360s. Vacuum-assisted venting is used in the initial stage of mold closing: specifically, when the mold closes to a pre-mold gap of 1.0mm, a vacuum is drawn to -0.08MPa and maintained for 60s before continuing mold closing and pressurization. The vacuum is maintained for the first 120s of the holding stage. During compression molding and curing, the BMC material flows under heat and pressure. A portion of the BMC material flows into the T-slot and undercut blind holes, forming a locking body embedded in the mechanical locking structure after curing. Simultaneously, the remaining BMC material cures to form a carbon fiber composite middle plate and local reinforcement areas located at corners, around button holes, connecting pillar areas, and around the large camera opening. This mechanically locks the aluminum alloy frame to the carbon fiber composite middle plate, resulting in a single integrated piece. For the T-slot area, BMC material is used to fill the T-slot to form an inverted embedded locking body; for the inverted blind hole area, BMC material is used to fill the inverted blind hole to form a blind hole inverted locking body.

[0063] Finally, the resulting monolithic part undergoes post-curing at 150℃ for 55 minutes. After post-curing, the monolithic part is CNC machined to form the assembly reference surface, side key holes, port holes, camera clearance area, and connection holes. During CNC machining, 0.10mm of allowance is removed from the sidewalls and 0.04mm of allowance is removed from the planes.

[0064] After CNC machining, a localized exposed area exists at the junction between the aluminum alloy outer frame and the carbon fiber composite middle plate. This exposed area is then sealed using a UV / thermal dual-curing epoxy edge sealant. The UV / thermal dual-curing epoxy edge sealant comprises, by total mass, 54 wt% bisphenol F epoxy resin, 26 wt% alicyclic epoxy resin, 3 wt% iodine salt photoinitiator, 4 wt% imidazole thermosetting agent, 10 wt% nano-silica, and 3 wt% additives. The bisphenol F epoxy resin has an epoxy equivalent of 170 g / eq; the alicyclic epoxy resin is 3,4-cyclic... The product comprises: oxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate; the iodonium salt photoinitiator is bis(4-tert-butylphenyl)iodonium tetra(pentafluorophenyl)borate; the imidazole thermosetting agent is 2-ethyl-4-methylimidazolium tetraphenylborate; the nano-silica is hydrophobically modified fumed silica with an average particle size of 20 nm; the additives include γ-glycidyl etheroxypropyltrimethoxysilane, polyether-modified polydimethylsiloxane leveling agent BYK-333, and polydimethylsiloxane defoamer, with a mass ratio of 2:0.5:0.5; the UV / thermal dual-curing epoxy sealing adhesive is irradiated with 800 mJ / cm² of 365 nm ultraviolet light. 2Then, it is cured at 90℃ for 25 minutes to form a sealing layer with a thickness of 22μm, thus obtaining an aluminum alloy-carbon fiber BMC composite frame.

[0065] Tests showed that the local column pull-out force of the aluminum alloy-carbon fiber BMC composite frame obtained in this embodiment was 812N, and the interface pushing failure load was 1.54kN / 100mm. After treatment at 85℃ and 85%RH for 240h, the interface shear strength retention rate was 88.4%. After a drop test at 1.6m on all six sides and twelve edges at the four corners, no penetrating delamination was observed.

[0066] Example 3

[0067] First, a 6063-T6 aluminum alloy frame substrate with external dimensions of 158.40mm × 74.50mm × 0.90mm is provided. A mechanical locking structure is formed on the side of the aluminum alloy frame substrate facing the carbon fiber composite middle plate using CNC milling. The mechanical locking structure includes a serrated groove on the inner wall of the long side of the aluminum alloy frame and through holes in the corner areas. The serrated groove has a tooth height of 0.22mm and a tooth pitch of 0.55mm; the through holes have an equivalent diameter of 0.58mm, and the spacing between adjacent through holes is 4.60mm.

[0068] Subsequently, the surface of the aluminum alloy outer frame substrate with the mechanical locking structure facing the carbon fiber composite middle plate was sequentially subjected to degreasing cleaning, deionized water washing, drying, and roughening treatment. The degreasing cleaning used a composite degreasing solution comprising 3.0% sodium carbonate, 1.0% fatty alcohol polyoxyethylene ether, and the remainder deionized water. The fatty alcohol polyoxyethylene ether was AEO-9, and the mass ratio of sodium carbonate to fatty alcohol polyoxyethylene ether was 3:1. The degreasing cleaning temperature was 52℃, and the degreasing cleaning time was 6 minutes. The drying temperature was 80℃, and the time was 10 minutes. The roughening treatment was carried out using fine sand blasting with white corundum as the blasting medium, a particle size of 180 mesh, a blasting pressure of 0.28 MPa, a blasting distance of 100 mm, and a blasting time of 15 seconds. After roughening treatment, the average profile micro-interval RSm of this side surface was 2.9 μm, and the ten-point height Rz was 1.3 μm. Then, the roughened aluminum alloy frame substrate is subjected to anodizing treatment using 160 g / L sulfuric acid as the electrolyte, a treatment voltage of 14 V, and a current density of 1.0 A / dm³. 2The processing time was 12 minutes, forming an anodic oxide layer with a thickness of 6.8 μm, which served as an inorganic insulating layer. Then, a composite solution of aminosilane and glycidyl ether silane with a mass ratio of 1:2 (0.8 wt%) was coated onto the surface of the anodic oxide layer; wherein the aminosilane was γ-aminopropyltriethoxysilane, and the glycidyl ether silane was γ-glycidyl etheroxypropyltrimethoxysilane, the solvent was ethanol / water with a mass ratio of 90:10, and the coating method was spraying. After coating, it was dried at 85°C for 8 minutes to form a silane layer with a thickness of 0.2 μm; subsequently, a surface density of 18 g / m³ was deposited on the silane layer. 2 An aramid felt is formed, and resin is impregnated into the aramid felt during subsequent molding processes to form a covering insulation layer with a total equivalent thickness of 22 μm, thus obtaining a volume resistivity of 10. 14 An insulating and corrosion-resistant interface layer with an Ω·cm thickness is used to obtain an aluminum alloy outer frame.

[0069] Next, the aluminum alloy outer frame is placed in a mold, which has a positioning cavity adapted to the shape of the aluminum alloy outer frame and a forming cavity corresponding to the carbon fiber composite middle plate. The forming cavity has dimensions of 149.40mm × 64.80mm × 0.55mm. Carbon fiber-containing SMC sheets are placed inside the aluminum alloy outer frame corresponding to the main plate forming area of ​​the carbon fiber composite middle plate to form a planar load-bearing area. Carbon fiber-containing BMC lumps are placed around the columns, corners, and USB openings to form local reinforcement areas.

[0070] After mold closing, compression molding and curing are performed at a temperature of 150℃, a pressure of 9.0MPa, and a holding time of 390s. Vacuum-assisted venting is used in the initial stage of mold closing: specifically, when the mold closes to a pre-mold gap of 1.0mm, a vacuum is drawn to -0.083MPa, maintained for 50s, and then mold closing and pressurization continue. The vacuum is maintained for the first 120s of the holding stage. During compression molding and curing, the SMC sheet and BMC lump flow under heat and pressure. A portion of the SMC and BMC materials flow into the sawtooth grooves and through holes, forming a locking body embedded in the mechanical locking structure after curing. Simultaneously, the cured SMC sheet forms the planar load-bearing area of ​​the carbon fiber composite middle plate, and the cured BMC lump forms local reinforcing areas around the columns, corners, and USB openings. This mechanically locks the aluminum alloy frame to the carbon fiber composite middle plate, resulting in a single integrated piece.

[0071] Finally, the resulting monolithic part undergoes post-curing at 158℃ for 60 minutes. After post-curing, the monolithic part is CNC machined to form the assembly reference surface, side key holes, port holes, camera clearance area, and connection holes. During CNC machining, 0.08mm of allowance is removed from the sidewalls and 0.04mm of allowance is removed from the planes.

[0072] After CNC machining, a localized exposed area exists at the junction between the aluminum alloy outer frame and the carbon fiber composite middle plate. This exposed area is then sealed with a fluorinated polyurethane-modified epoxy sealant. Based on the total mass of the fluorinated polyurethane-modified epoxy sealant, it comprises: 35wt% terminal epoxy-terminated fluorinated polyurethane-modified epoxy resin, 32wt% bisphenol F epoxy resin (epoxy equivalent of 170 g / eq), 10wt% 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, 15wt% isophorone diamine-modified alicyclic amine adduct, 5wt% hydrophobically modified fumed silica, 1.5wt% γ-glycidyl etheroxypropyltrimethoxysilane, and polyether-modified... The mixture contains 0.8 wt% of polydimethylsiloxane leveling agent BYK-333 and 0.7 wt% of polydimethylsiloxane defoamer; wherein the epoxy-terminated fluorinated polyurethane modified epoxy resin is an epoxy-terminated fluorinated polyurethane prepolymer obtained by reacting hydroxyl-terminated perfluoropolyether diol, isophorone diisocyanate and glycidyl ether type hydroxyl epoxy monomer, wherein the number average molecular weight of the hydroxyl-terminated perfluoropolyether diol is 1500, the glycidyl ether type hydroxyl epoxy monomer is 2-hydroxyethyl glycidyl ether, and the average particle size of the hydrophobic modified fumed silica is 20 nm. After dispensing, the mixture is cured at 75 °C for 50 min to form an edge sealing layer with a thickness of 18 μm, thus obtaining an aluminum alloy-carbon fiber SMC / BMC composite middle frame.

[0073] Tests showed that the tensile modulus of the aluminum alloy-carbon fiber SMC / BMC composite midframe obtained in this embodiment was 30.2 GPa, the flexural modulus was 29.1 GPa, the stud pull-out force was 965 N, and the position accuracy of the key hole was 0.04 mm. After the whole machine was assembled, it was dropped 26 times in various postures from 1.5 m, and no visible cracks or interface warping appeared around the camera opening.

[0074] Example 4

[0075] First, a 6082-T6 aluminum alloy frame substrate with external dimensions of 160.00mm × 75.50mm × 0.98mm is provided. A mechanical locking structure is formed on the side of the aluminum alloy frame substrate facing the carbon fiber composite middle plate using CNC milling. The mechanical locking structure is a dovetail groove located on the inner wall of the aluminum alloy frame. The dovetail groove has an opening width of 0.50mm, a cavity bottom width of 0.95mm, a structural depth of 0.55mm, and a pitch of 3.00mm between adjacent dovetail grooves.

[0076] Subsequently, the surface of the aluminum alloy outer frame substrate with the mechanical locking structure facing the carbon fiber composite middle plate was sequentially subjected to degreasing cleaning, deionized water washing, drying, and roughening treatment. The degreasing cleaning, deionized water washing, and drying were the same as in Example 1; the roughening treatment employed femtosecond laser texturing with a laser wavelength of 1030 nm, a pulse width of 350 fs, a scanning interval of 25 μm, and a scanning speed of 600 mm / s, forming periodic micro-pits and reverse-entry bridge-like microstructures. Then, the roughened aluminum alloy outer frame substrate was subjected to plasma electrolytic oxidation treatment. The electrolyte was an aqueous solution containing 7 g / L sodium silicate, 2 g / L potassium hydroxide, and 1.5 g / L sodium phosphate. The treatment voltage was 410 V, and the current density was 5.8 A / dm³. 2 The processing time was 3.5 min, forming a 7.5 μm thick PEO insulating layer, which served as an inorganic insulating layer. Then, a 1.2 wt% (w / w) composite solution of aminosilane and glycidyl ether silane was coated onto the surface of the PEO insulating layer, with a mass ratio of 1:2. The aminosilane was γ-aminopropyltriethoxysilane, and the glycidyl ether silane was γ-glycidyl etheroxypropyltrimethoxysilane. The solvents were ethanol and water, with a mass ratio of 90:10. The coating method was spraying, and after coating, it was dried at 90°C for 10 min to form a 0.25 μm thick silane layer. Subsequently, a surface density of 18 g / m² was laid on the silane layer. 2 An aramid felt is formed, and resin is impregnated into the aramid felt during subsequent molding processes to form a covering insulation layer with a total equivalent thickness of 22 μm, thus obtaining a volume resistivity of 10. 9 An insulating and corrosion-resistant interface layer with an Ω·cm thickness is used to obtain an aluminum alloy outer frame.

[0077] Next, the aluminum alloy outer frame is placed in the mold, which has a positioning cavity adapted to the shape of the aluminum alloy outer frame and a forming cavity corresponding to the carbon fiber composite middle plate. The dimensions of the forming cavity are 149.40mm×64.80mm×0.55mm. 18.6g of SMC sheet is placed inside the aluminum alloy outer frame, corresponding to the forming area of ​​the main plate of the carbon fiber composite middle plate. After the mold is closed, a molding and curing process is performed. The molding and curing process is performed at a temperature of 152℃, a pressure of 10.5MPa, and a holding time of 430s. Vacuum-assisted venting is used in the initial stage of mold closing. Specifically, when the mold is closed to a pre-mold gap of 0.8mm, a vacuum is drawn to -0.083MPa and maintained for 50s. Then, the mold is closed and pressure is applied. The vacuum is maintained for the first 130s of the holding stage. During the molding and curing process, the SMC sheet flows after being heated and pressed. A portion of the SMC material flows into the dovetail groove and forms a locking body embedded in the mechanical locking structure after curing. At the same time, the remaining SMC material cures to form a carbon fiber composite middle plate, thereby forming a mechanical locking connection between the aluminum alloy outer frame and the carbon fiber composite middle plate, resulting in a single piece.

[0078] Finally, the resulting monolithic part undergoes post-curing at 160℃ for 45 minutes. After post-curing, the monolithic part is CNC machined to form the assembly reference surface, side key holes, port holes, camera clearance area, and connection holes. During CNC machining, 0.10mm of allowance is removed from the sidewalls and 0.05mm of allowance is removed from the planes.

[0079] After CNC machining, a localized exposed area exists at the interface between the aluminum alloy outer frame and the carbon fiber composite middle plate. This exposed area is cleaned, and areas where Parylene edge sealing is not required are temporarily masked. The workpiece is then placed in a Parylene deposition apparatus for edge sealing using chemical vapor deposition. The dimer used in the Parylene deposition is Parylene C dimer, i.e., dichlorodimer p-xylene. The dimer has a sublimation temperature of 150°C, a pyrolysis temperature of 650°C, and a deposition pressure of 20 Pa, allowing Parylene C monomers to polymerize and deposit on the interface surface at room temperature, forming an 8 μm thick Parylene C edge sealing layer. Subsequently, the aluminum alloy outer surface undergoes masking sandblasting and a low-temperature transparent coating treatment. The masking sandblasting includes: first, applying polyimide heat-resistant tape, silicone plugs, and peelable masking adhesive to the Parylene C surface. The C-side sealing layer, exposed areas of the carbon fiber composite middle plate, assembly reference surface, side key holes, port holes, camera clearance areas, and connection holes are masked, leaving only the aluminum alloy exterior surface as the sandblasting area. Then, using 240-mesh glass microspheres as the sandblasting medium, the aluminum alloy exterior surface is slightly matte-finished under the conditions of a sandblasting pressure of 0.15 MPa, a sandblasting distance of 120 mm, a sandblasting angle of 60°, and a single-sided sandblasting time of 12 s, resulting in a surface roughness Ra of 0.45 μm. After sandblasting, anhydrous ethanol is used for wiping and ion air dust removal to remove residual dust. The low-temperature transparent coating treatment includes: spraying a low-temperature curing transparent polyurethane acrylate coating onto the sandblasted aluminum alloy exterior surface. The dry film thickness of the transparent coating is 12 μm. After spraying, it is leveled at room temperature for 5 min, and then cured at 80°C for 30 min to obtain an aluminum alloy-carbon fiber SMC / BMC composite middle frame.

[0080] Testing revealed that the initial interfacial shear strength of the aluminum alloy-carbon fiber SMC / BMC composite frame obtained in this embodiment was 34.1 MPa; after 500 thermal cycles at -30℃ / 80℃, the interfacial shear strength retention rate was 90.3%; and the three-point bending equivalent stiffness was 17.6% higher than that of the all-aluminum reference component of the same thickness. This embodiment demonstrates that the superposition of the laser-induced bridge-like microstructure and the macroscopic dovetail groove can simultaneously apply three strengthening mechanisms—microscopic wetting, mesoscopic interlocking, and macroscopic undercut—to the same interface, significantly enhancing interfacial bonding performance and structural stiffness.

[0081] Example 5

[0082] First, a 6061-T6 aluminum alloy outer frame substrate is provided. A mechanical locking structure is formed on the side of the aluminum alloy outer frame substrate facing the composite middle plate using CNC milling and drilling. The mechanical locking structure includes dovetail grooves along the inner circumferential wall of the aluminum alloy outer frame and through holes distributed in localized areas. In the middle, the opening width of the dovetail groove is 0.46mm, the bottom width of the cavity is 0.82mm, and the structural depth is 0.50mm; The equivalent diameter of the through hole is 0.62 mm, and the spacing between adjacent through holes is 5.2 mm.

[0083] Subsequently, the surface of the aluminum alloy outer frame base with the mechanical locking structure facing the composite middle plate was then... The aluminum alloy frame substrate underwent degreasing, cleaning, deionized water washing, drying, and roughening treatment (same as in Example 1) to obtain a roughened interface with an average profile micro-interface spacing RSm of 4.2 μm and a ten-point height Rz of 2.1 μm. Then, the roughened aluminum alloy frame substrate was subjected to micro-arc oxidation treatment. This micro-arc oxidation treatment included: firstly, using polyimide heat-resistant tape and silicone plugs to temporarily shield the surface areas, pre-processed areas of the assembly reference surfaces, and hole areas of the aluminum alloy frame substrate that did not require micro-arc oxidation layer formation, exposing only the connection area facing the carbon fiber composite middle plate; using the aluminum alloy frame substrate as the anode and the stainless steel tank as the cathode, a pulsed micro-arc oxidation power supply was used for treatment; the micro-arc oxidation electrolyte was an aqueous solution containing 7.5 g / L sodium silicate, 2.5 g / L potassium hydroxide, 1.5 g / L sodium hexametaphosphate, and 1.0 g / L sodium aluminate, with the electrolyte temperature controlled at 30°C, the treatment voltage at 410 V, and the current density at 5.5 A / dm³. 2 The pulse frequency was 500Hz, the duty cycle was 20%, and the processing time was 3.8min. During the processing, circulating cooling and mechanical stirring were used to maintain a stable electrolyte temperature. After processing, the aluminum alloy frame substrate was sequentially rinsed with deionized water and dried with hot air at 60℃ for 10min to form a micro-arc oxide layer with a thickness of 8.0μm, which served as an inorganic insulating layer. Subsequently, a coupling undercoating layer with a thickness of 0.3μm (same as in Example 1) was constructed on the surface of the micro-arc oxide layer. Then, a surface density of 20g / m² was laid on the coupling undercoating layer. 2 A glass fiber mat is formed, and resin is impregnated into the glass fiber mat during subsequent molding to form a covering insulating layer with a total equivalent thickness of 22 μm. This results in a covering insulating layer with a volume resistivity of 10⁻⁶. 10 An insulating and corrosion-resistant interface layer with an Ω·cm thickness is used to obtain an aluminum alloy outer frame.

[0084] Next, the aluminum alloy frame is placed in a mold. The mold has a positioning cavity adapted to the shape of the aluminum alloy frame and a forming cavity corresponding to the composite middle plate. The dimensions of the forming cavity are 149.40mm × 64.80mm × 0.55mm. Carbon fiber-containing SMC sheets are laid on the main body plate. A non-conductive reinforcement area is set in the antenna avoidance area, and a glass fiber BMC slub is laid in the non-conductive reinforcement area. Based on the total mass of the glass fiber BMC slub, the glass fiber BMC slub comprises 28.0wt% alkali-free chopped glass fiber, 44.0wt% low-dielectric epoxy / benzoxazine composite resin system, 8.0wt% hollow glass microspheres, 10.0wt% spherical fused silica, 7.0wt% latent curing accelerator system, 1.2wt% silane coupling agent, and 1.8wt% molding aid. The alkali-free chopped glass fiber has a length of 6mm and is a single filament. The diameter is 11 μm; the low-dielectric epoxy / benzoxazine composite resin system is composed of dicyclopentadiene epoxy resin, hydrogenated bisphenol A epoxy resin, and bisphenol F benzoxazine resin, with a mass ratio of 45:25:30; the hollow glass microspheres have an average particle size of 20 μm, and the spherical fused silica has an average particle size of 3 μm; the latent curing accelerator system consists of dicyandiamide, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, and 2... The silane coupling agent is composed of γ-glycidyl etheroxypropyltrimethoxysilane and phenyltrimethoxysilane in a mass ratio of 1:1; the molding aid is composed of zinc stearate, polyethylene wax, and polyether-modified polydimethylsiloxane (BYK-333) in a mass ratio of 5:3:2. The closest distance between the non-conductive reinforcement area and the breakpoints of the upper and lower antennas is 7.5 mm.

[0085] After mold closing, compression molding and curing are performed at a temperature of 147℃, a pressure of 8.8MPa, and a holding time of 410s. When the mold is closed to a pre-mold gap of 0.9mm, a vacuum is drawn to -0.082MPa and maintained for 40s before mold closing and pressurization continue. During the molding process, some SMC and BMC materials flow into the dovetail groove and through hole, forming a locked body after curing. At the same time, the SMC material cures to form the main load-bearing area of ​​the carbon fiber body, and the BMC material cures to form the non-conductive reinforcement area of ​​the antenna region, thereby forming a mechanically locked connection between the aluminum alloy frame and the composite middle plate, resulting in a single piece.

[0086] Subsequently, the resulting integral part undergoes post-curing treatment at a temperature of 155℃. The curing time is 60 minutes. After post-curing, the integral part is CNC machined to form the assembly reference surface, side key holes, port holes, camera clearance space, and connection holes. During CNC machining, the sidewall allowance is reduced by 0.10 mm, and the plane allowance is reduced by 0.04 mm.

[0087] After CNC machining, the locally exposed area at the junction of the aluminum alloy outer frame and the composite middle plate is sealed with low-dielectric epoxy sealant. The low-dielectric epoxy sealant comprises, by total mass, 38 wt% dicyclopentadiene epoxy resin, 20 wt% hydrogenated bisphenol A epoxy resin, 10 wt% alicyclic epoxy resin, 5 wt% terminal epoxy group phenylsiloxane modified resin, 16 wt% isophorone diamine modified alicyclic amine adduct, 4 wt% hollow glass microspheres, 3 wt% spherical fused silica, 2 wt% hydrophobically modified fumed silica, 1 wt% phenyltrimethoxysilane, and 0.7 wt% γ-glycidyl etheroxypropyltrimethoxysilane. The epoxy resin contains 0.3 wt% of 2,4,6-tris(dimethylaminomethyl)phenol; wherein the epoxy equivalent of the dicyclopentadiene-type epoxy resin is 250 g / eq, the epoxy equivalent of the hydrogenated bisphenol A epoxy resin is 220 g / eq, the alicyclic epoxy resin is 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate, the average particle size of the hollow glass microspheres is 20 μm, the average particle size of the spherical fused silica is 3 μm, and the average particle size of the hydrophobic modified fumed silica is 20 nm; after dispensing, it is cured at 85°C for 35 min to form a 16 μm thick low-dielectric epoxy sealing layer, thus obtaining an aluminum alloy-carbon fiber SMC / BMC composite frame.

[0088] Testing showed that the aluminum alloy-carbon fiber SMC / BMC composite frame obtained in this embodiment passed 500V insulation tests. The interface insulation resistance under the test conditions was 8.7 × 10⁻⁶. 10 Ω; Compared with an all-aluminum reference component of the same size, the average decrease in total OTA efficiency in the 1~3GHz band is 0.22dB; the overall frame weight is reduced by 13.1%. This embodiment shows that by using a carbon fiber SMC structure in the main load-bearing area and a glass fiber BMC non-conductive reinforcement structure in the antenna avoidance area, combined with an insulating and anti-corrosion interface layer and a mechanical locking structure design, it is possible to maintain the load-bearing advantages and lightweight effect of the carbon fiber main body while taking into account the electromagnetic performance requirements of the antenna area, thus achieving a synergistic improvement in structural performance, insulation performance and wireless communication performance.

[0089] Example 6

[0090] First, a 6061-T6 aluminum alloy outer frame substrate is provided. A mechanical locking structure is formed on the side of the aluminum alloy outer frame substrate facing the composite middle plate using CNC milling and drilling. The mechanical locking structure includes an undercut blind hole and a serrated groove. The undercut blind hole has an inlet diameter of 0.40 mm, a bottom diameter of 0.76 mm, and a hole depth of 0.65 mm; the serrated groove has a tooth height of 0.35 mm and a tooth pitch of 1.20 mm.

[0091] Subsequently, the surface of the aluminum alloy outer frame substrate with the mechanical locking structure facing the composite middle plate was degreased, washed with deionized water, dried, and roughened (same as in Example 1) to obtain a roughened interface with an average profile micro-pitch RSm of 5.2 μm and a ten-point height Rz of 1.8 μm. Then, the roughened aluminum alloy outer frame substrate was subjected to plasma electrolytic oxidation treatment (same as in Example 1) to form a 9.1 μm thick PEO insulating layer, which serves as an inorganic insulating layer. Subsequently, a ceramic-filled epoxy insulating primer was coated onto the surface of the PEO insulating layer (same as in Example 2) to form a 15 μm thick covering insulating layer, thus obtaining a volume resistivity of 10. 11 An insulating and corrosion-resistant interface layer with an Ω·cm thickness is used to obtain an aluminum alloy outer frame.

[0092] Next, the aluminum alloy outer frame is placed in the mold, which has a positioning cavity adapted to the shape of the aluminum alloy outer frame and a forming cavity corresponding to the carbon fiber composite middle plate. The dimensions of the forming cavity are 150.6mm × 66.3mm × 0.62mm. 18.3g of SMC sheet containing carbon fiber is placed inside the aluminum alloy outer frame, corresponding to the forming area of ​​the main plate of the carbon fiber composite middle plate. After the mold is closed, a molding and curing treatment is performed. The molding and curing treatment temperature is 154℃, the pressure is 11.2MPa, and the holding time is 360s. Vacuum-assisted venting is used in the initial stage of mold closing. Specifically, when the mold is closed to the pre-mold closing gap of 0.85mm, a vacuum is drawn to -0.088MPa and maintained for 45s. Then, the mold is closed and pressure is applied. The vacuum is maintained for the first 120s of the holding stage. During the molding and curing process, the SMC sheet flows after being heated and pressed. A portion of the SMC material flows into the undercut blind holes and serrated grooves, and after curing, it forms a locking body embedded in the mechanical locking structure. At the same time, the remaining SMC material cures to form a carbon fiber composite middle plate, thereby forming a mechanical locking connection between the aluminum alloy outer frame and the carbon fiber composite middle plate, resulting in a single piece.

[0093] Subsequently, the resulting monolithic part underwent post-curing at 145℃ for 60 minutes. After post-curing, the monolithic part was CNC machined to form the assembly reference surface, side key holes, port holes, camera clearance area, and connection holes. During CNC machining, 0.11mm of allowance was removed from the sidewalls and 0.05mm of allowance was removed from the planes.

[0094] After CNC machining, a localized exposed area exists at the junction between the aluminum alloy outer frame and the carbon fiber composite middle plate. This exposed area is then sealed with an edge-sealing adhesive made of fluorinated polymer-modified epoxy, comprising fluorinated acrylic resin, bisphenol F epoxy resin, alicyclic amine curing agent, and nano-silica in a mass ratio of 20:100:30:4. The fluorinated acrylic resin is an epoxy-modified fluorinated acrylic copolymer, which is obtained by copolymerizing trifluoroethyl methacrylate, glycidyl methacrylate, and methyl methacrylate. The fluorine content is 16wt%, and the epoxy equivalent is 780g / eq; the bisphenol F epoxy resin is a liquid bisphenol F type epoxy resin with an epoxy equivalent of 170g / eq and a viscosity of 3500mPa·s at 25℃; the alicyclic amine curing agent is an isophorone diamine modified alicyclic amine adduct; the nano silica is hydrophobically modified fumed silica with an average particle size of 20nm. After dispensing, it is cured at 80℃ for 45min to form a fluorinated polymer edge sealing layer with a width of 0.42mm and a thickness of 12μm, thus obtaining an aluminum alloy-carbon fiber SMC composite frame.

[0095] Testing revealed that the aluminum alloy-carbon fiber SMC composite frame obtained in this embodiment exhibited an edge corrosion expansion width of 0.07 mm after 240 hours of neutral salt spray testing; the percentage of abnormal area at the interface detected by ultrasonic C-scan was 0.3%; and the interface shear strength retention rate was 86.9% after 500 hours of humid heat treatment at 85℃ / 85%RH. This embodiment demonstrates that a multi-level insulation protection system constructed using a PEO insulation layer, a ceramic-filled epoxy insulation layer, and a fluorinated polymer-modified epoxy edge sealing layer can effectively inhibit the penetration of moisture and corrosive media along the interface, significantly improving the boundary corrosion resistance and long-term reliability of the composite frame in humid heat environments. Furthermore, the mechanical locking structure formed by the undercut blind holes and serrated grooves further enhances the interface connection stability and service reliability.

[0096] Comparative Example 1 This comparative example is basically the same as Example 1, except that: in this comparative example, the side of the aluminum alloy outer frame substrate facing the carbon fiber composite middle plate is not machined with dovetail grooves, through holes, or other mechanical locking structures. Only the surface of the aluminum alloy outer frame substrate facing the carbon fiber composite middle plate is subjected to the same cleaning, roughening treatment, and insulation and anti-corrosion interface layer construction treatment as in Example 1. Subsequently, the same SMC sheet as in Example 1 is placed inside the aluminum alloy outer frame corresponding to the main plate forming area of ​​the carbon fiber composite middle plate. Prepared under the same molding, curing, post-curing, CNC machining, and edge sealing conditions as in Example 1. The composite mobile phone frame is obtained.

[0097] The initial interfacial shear strength of the composite mobile phone frame obtained in this comparative example was 12.9 MPa. After treatment at 85℃ and 85%RH for 240 hours, the interfacial shear strength retention rate was 54.8%. After a 1.2m drop test, an interfacial warping with a length of 18.4 mm appeared on the long side. These results indicate that, without a mechanical locking structure, the bonding between the aluminum alloy frame and the carbon fiber composite mid-plate relies mainly on interfacial adhesion, resulting in significantly reduced shear resistance and resistance to drop warping.

[0098] Comparative Example 2 This comparative example is basically the same as Example 1, except that: in this comparative example, no insulating and anti-corrosion interface layer is constructed on the side of the aluminum alloy outer frame substrate with mechanical locking structure facing the carbon fiber composite middle plate, and no edge sealing treatment is performed after CNC machining, resulting in direct conductive contact and interface exposure risk between the carbon fiber composite middle plate and the aluminum alloy outer frame. The remaining mechanical locking structure, SMC sheet, molding curing, post-curing, and CNC machining conditions are the same as in Example 1.

[0099] The initial interfacial shear strength of the composite mobile phone frame obtained in this comparative example was 28.2 MPa. After 96 hours of neutral salt spray testing, the edge corrosion propagation width reached 1.46 mm. After 240 hours of treatment under 85℃ and 85%RH humid heat conditions, the interfacial shear strength retention rate was 63.2%, and white corrosion products were visible locally at the interface. These results indicate that although the mechanical interlocking structure can improve the initial connection strength, In the absence of an insulating and anti-corrosion interface layer and an edge sealing layer, contact corrosion is likely to occur between aluminum alloy and carbon fiber. Corrosion leads to a decrease in interface reliability under humid, hot, and salt spray environments.

[0100] In summary, this invention achieves a stable connection between the aluminum alloy outer frame and the carbon fiber composite middle plate through the combination of mechanical locking structure, insulating and anti-corrosion interface layer, SMC and / or BMC molding and curing filling, CNC machining and edge sealing treatment, and improves the composite mobile phone middle frame's resistance to interface peeling, corrosion resistance and processing and assembly accuracy. The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. An aluminum alloy-carbon fiber SMC / BMC composite mid-frame, characterized in that, It includes an aluminum alloy outer frame and a carbon fiber composite middle plate disposed inside the aluminum alloy outer frame; The aluminum alloy outer frame is provided with a mechanical locking structure on the side facing the carbon fiber composite middle plate; The carbon fiber composite middle plate is formed by molding and curing carbon fiber-containing SMC and / or BMC; during the molding and curing process, a portion of the SMC and / or BMC flows into the mechanical locking structure and is cured to form a locking body, thereby forming a mechanical locking connection between the aluminum alloy outer frame and the carbon fiber composite middle plate, constituting an integral part; The integrated component, after being CNC machined, has one or more of the following: an assembly reference surface, side key holes, port holes, camera clearance positions, and connection holes; An insulating and corrosion-resistant interface layer is provided between the aluminum alloy outer frame and the carbon fiber composite middle plate.

2. The aluminum alloy-carbon fiber SMC / BMC composite mid-frame according to claim 1, characterized in that, The aluminum alloy outer frame is made of one or more of the following: aluminum-magnesium alloy, aluminum-magnesium-silicon alloy, aluminum-zinc-magnesium alloy, aluminum-zinc-magnesium-copper alloy, and aluminum-silicon cast aluminum alloy. The mechanical locking structure is one or more of the following: dovetail groove, T-groove, serrated groove, undercut hole, undercut blind hole, and through hole.

3. The aluminum alloy-carbon fiber SMC / BMC composite mid-frame according to claim 1, characterized in that, The aluminum alloy outer frame also has a roughened interface in the area where the mechanical locking structure is set; The average profile micro-pitch RSm of the roughened interface is 0.8~10μm, and the ten-point height Rz is 0.2~5μm; and / or, the roughened interface has an inverted snap-like microstructure, a reverse-entry bridge-like microstructure, or a concave-convex interlocking microstructure.

4. The aluminum alloy-carbon fiber SMC / BMC composite mid-frame according to claim 1, characterized in that, The insulating and corrosion-resistant interface layer includes an inorganic insulating layer disposed on the surface of the aluminum alloy outer frame, and a covering insulating layer disposed on the inorganic insulating layer; The inorganic insulating layer is one or more of the following: insulating oxide layer, ceramic layer and chemical conversion layer; The covering insulation layer is one or more of the following: coupling primer layer, resin enrichment layer, inorganic filler insulation layer, glass fiber isolation layer and aramid isolation layer; The total thickness of the insulating and anti-corrosion interface layer is 5~100μm, wherein the thickness of the inorganic insulating layer is 2~30μm, and the thickness of the covering insulating layer is 3~70μm; The volume resistivity of the insulating and corrosion-resistant interface layer is 10. 8 ~10 14 Ω·cm.

5. The aluminum alloy-carbon fiber SMC / BMC composite midframe according to claim 1, characterized in that... It lies in, The matrix resin of the carbon fiber composite medium plate is one or more of epoxy resin, vinyl ester resin, benzoxazine resin, cyanate ester resin and phenolic resin. The carbon fiber in the carbon fiber composite plate has a mass fraction of 20-70% and a length of 3-50 mm.

6. The aluminum alloy-carbon fiber SMC / BMC composite mid-frame according to claim 1, characterized in that, The carbon fiber composite mid-plate includes a planar load-bearing area formed by SMC and a localized reinforcing area formed by BMC. The planar load-bearing area is located on the main body panel area inside the aluminum alloy outer frame; The local reinforcement area is located at one or more of the following positions: corner, connecting column, local rib, perimeter of hole, and perimeter of large opening of camera.

7. The aluminum alloy-carbon fiber SMC / BMC composite mid-frame according to claim 1, characterized in that, A junction is formed between the aluminum alloy outer frame and the carbon fiber composite middle plate, and the area exposed after CNC machining in the junction is provided with an edge sealing layer. The edge sealing layer is one or more of epoxy edge sealing layer, fluorinated polymer edge sealing layer, polyimide edge sealing layer and phenelzine edge sealing layer, and the thickness of the edge sealing layer is 5~80μm.

8. The method for preparing the aluminum alloy-carbon fiber SMC / BMC composite midframe according to any one of claims 1 to 7, characterized in that, Includes the following steps: S1. Provide an aluminum alloy outer frame substrate, and process a mechanical locking structure on the side of the aluminum alloy outer frame substrate facing the carbon fiber composite middle plate; S2. The aluminum alloy outer frame substrate with mechanical locking structure obtained in step S1 is cleaned and roughened on the side facing the carbon fiber composite middle plate, and an insulating and anti-corrosion interface layer is constructed on this side surface to obtain the aluminum alloy outer frame. S3. Place the aluminum alloy outer frame in the mold, and place the SMC sheet containing carbon fiber and / or BMC pellets inside the aluminum alloy outer frame corresponding to the forming area of ​​the carbon fiber composite middle plate. Perform molding and curing treatment, so that the SMC sheet and / or BMC pellets flow into the mechanical locking structure and solidify to form a locking body during the molding and curing process. At the same time, the carbon fiber composite middle plate is solidified to form a carbon fiber composite middle plate, thereby forming a mechanical locking connection between the aluminum alloy outer frame and the carbon fiber composite middle plate to obtain an integral part. S4. Perform post-curing treatment and CNC machining on the integral part in sequence to form an assembly datum. One or more of the following: front panel, side key hole, port hole, camera clearance position, and connection hole; S5. The junction between the exposed aluminum alloy frame and the carbon fiber composite middle plate after CNC machining. Edge sealing is performed to obtain an aluminum alloy-carbon fiber SMC / BMC composite mid-frame.

9. The preparation method according to claim 8, characterized in that, The temperature of the molding and curing process in step S3 is 120~180℃, the pressure is 3~30MPa, the holding time is 60~900s, and vacuum-assisted degassing is used during the molding and curing process. The post-curing treatment in step S4 is performed at a temperature of 140~170℃ for 40~90 minutes.

10. The application of the aluminum alloy-carbon fiber SMC / BMC composite mid-frame according to any one of claims 1 to 7 in mobile phones, tablets, laptops, drones, robot terminals, AR or VR devices.